Total Synthesis of Alkaloid 205B - Tsukanov, Sergey V. (American Chemical Society, 2014)
[Image: see text] Concise and highly stereocontrolled total syntheses of racemic and enantiopure frog alkaloid 205B (1) were accomplished in 11 steps from 4-methoxypyridines 6 and 7 in overall yields of 8 and 8%, respectively. The assembly of the core of the natural product relies on a stereoselective Tsuji–Trost allylic amination reaction and a ring-closing metathesis. The synthesis features the use of an N-acylpyridinium salt reaction to introduce the first stereocenter and an unprecedented trifluoroacetic anhydride-mediated addition of an allylstannane to a vinylogous amide with complete facial selectivity. Deoxygenation of the C4 ketone proved difficult but was accomplished via a modified Barton–McCombie reaction in the presence of a catalytic amount of diphenyl diselenide.